Giant hand lipoma: a surgical challenge - Katherine Santacoloma; Gabriella Mazzarone de Sá Barreto; Guillermo Loda; Marcela Duarte Benez Miller (Sociedade Brasileira de Dermatologia (SBD), 2021)
Lipomas are frequent soft tissue tumors and can be found anywhere in the body; however, their location in hand is rare. They are called giants when they exceed 5 cm. In these cases, the differential diagnosis must be made with liposarcoma. These benign tumors must be characterized preoperatively with an imaging study, and their treatment is surgical. We present the case of a patient with a giant hand lipoma successfully treated with a modified Bruner incision approach.